Gas separation performance of poly(4-vinylpyridine)/polyetherimide composite hollow fibers - Shieh, J-J; Chung, T-S; Wang, R.; Srinivasan, M.P.; Paul, D.R.
The preparation and gas permeation performance (H2, CO2, O2, N2, CH4)of silicone rubber/poly(4-vinylpyridine)/polyetherimide (SR/P4VP/PEI)multi-layer composite hollow fiber membranes are described. Dilute P4VP solutions form a defective coating layer on the top of PEI hollow fiber surface but reduce the surface porosity significantly, which makes the SR plugging feasible to regain the gas permselectivity of P4VP/PEI composite hollow fiber. Polyethylene glycol (PEG)additive in the PEI spinning dopes suppresses the growth of macro-voids and produces a membrane morphology having a more porous skin surface and more compact substructure, which provides a lower skin resistance and a higher substructure resistance for gas permeation. Substantial substructure resistance can deteriorate the membrane performance. Since the unfavorable influence of substructure resistance on the gas permeance is more pronounced for the fast permeating gas and in the order of H2>CO2>O2>N2>CH4, the gas selectivities of H2/N2, CO2/CH4, and O2/N2 decrease accordingly. The PEI hollow fibers prepared from a PEI/PEG/NMP (23/0/77)spinning dope, after coated with 0.2 wt.
Keywords: MEMBRANE FABRICATION; HOLLOW FIBER COMPOSITE; GAS SEPARATION; SUBSTRUCTURE RESISTANCE; POLYETHERIMIDE; POLY(4-VINYLPYRIDINE)